PENDIDIKAN KESEHATAN TETANG SIROSIS HEPATIS PADA PEMUDA DUSUN NYAMPLUNG KRADENAN SRIMULYO PIYUNGAN BANTUL - sangadji, faisal (ABDIMAS Madani, 2022)
ABSTRACT Hepatic cirrhosis is a pathological condition that describes the final stage of progressive hepatic fibrosis. Damage to these liver cells will continue to cause liver structure disorders and increased vascularity which causes varicose veins or vascular dilation in the stomach and esophagus. According to reports from public hospitals in Indonesia, the average incidence of liver cirrhosis is 3.5% of all patients treated in the internal medicine room, or an average of 47.4% of all patients with liver disease treated (Kusumobroto, 2007). Patients with liver cirrhosis who were treated in the internal medicine room at Dr. Sardjito Yogyakarta around 4.1% in a period of 1 year. Liver cirrhosis is closely related to alcoholic liver disease (PHA). PHA is a liver function disorder caused by consuming alcohol for a long time with a certain amount. Of some heavy alcohol drinkers, about 10-30% will develop alcoholic hepatitis sufferers, and will continue to develop into cirrhosis if there is no intervention. Keywords: Youth, cirrhosis, alcohol.